Adalimumab in the treatment of plaque-type psoriasis and psoriatic arthritis. (September 2013) - Saraceno, Rosita; Bavetta, Mauro; Zangrilli, Arianna; Chiricozzi, Andrea; Potenza, Concetta; Chimenti, Sergio; Chimenti, Maria Sole
Abstract : Introduction: Psoriasis and psoriatic arthritis (PsA) are chronic immune-mediated diseases, and TNF-α (tumor necrosis factor) is a pro-inflammatory cytokine that plays a critical role in the pathogenesis of these conditions.Adalimumab is an anti-TNF-α drug widely used for the treatment of both psoriasis and PsA. Controlled clinical trials demonstrated that adalimumab is characterized by a high degree of clinical response. The aim of this review is to report the safety, efficacy, and recent findings in the treatment of psoriasis and PsA with adalimumab. Areas covered: This article reviews the results of Phase II, III, controlled, and observational clinical studies on adalimumab in the treatment of psoriasis and PsA. A systematic search was conducted using the Pubmed Medline database for primary articles. Expert opinion: Treatment of psoriasis and PsA represents a therapeutic challenge for dermatologists and rheumatologists. The efficacy, tolerability, and safety profiles suggest adalimumab as a suitable anti-psoriatic drug in the long-term treatment of psoriasis and PsA. Management of long-term treatment, loss of efficacy, and comorbidities has been described.